1996
DOI: 10.1002/j.1939-4640.1996.tb01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Image Analysis System to Monitor the Retention of Residual Cytoplasm by Human Spermatozoa: Correlation With Biochemical Markers of the Cytoplasmic Space, Oxidative Stress, and Sperm Function

Emilio Gomez,
Donna W. Buckingham,
James Brindle
et al.

Abstract: A method has been developed for quantifying the residual cytoplasm present in the midpiece of human spermatozoa, based upon the imaging of NADH oxidoreductase activity. This procedure used NADH and nitroblue tetrazolium as electron donor and acceptor, respectively, and resulted in the discrete staining of the entire midpiece area, including the residual cytoplasm. Image analysis techniques were then used to generate binary images of the midpiece, from which objective measurements of this cellular domain could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Creatinine kinase (CK) and G6PDH were used as biomarkers of this retention [33][34][35][36]. In addition, it has been reported that in an environment of increased RONS levels, immature sperm can cause OS in neighboring mature ones during their transit through the epididymis [37][38][39]. Also, mature sperm could be an additional source of RONS due to cellular metabolism [40].…”
Section: Sources Of Rons In Semenmentioning
confidence: 99%
See 1 more Smart Citation
“…Creatinine kinase (CK) and G6PDH were used as biomarkers of this retention [33][34][35][36]. In addition, it has been reported that in an environment of increased RONS levels, immature sperm can cause OS in neighboring mature ones during their transit through the epididymis [37][38][39]. Also, mature sperm could be an additional source of RONS due to cellular metabolism [40].…”
Section: Sources Of Rons In Semenmentioning
confidence: 99%
“…There is a positive correlation between RONS production, anomalies in sperm morphology, and DNA damage [31,38,49]. High levels of expression of the isoform of NADPH oxidase (NOX)-NOX5, generators of RONS in sperm-have been reported in both teratozoospermia [50] and asthenozoospermic human ejaculates [37].…”
Section: Sources Of Rons In Semenmentioning
confidence: 99%